Platelet-Rich Plasma (PRP) Allogenic: A Potential Challenge for Decreasing Random Blood Glucose, Uric Acid, and Cholesterol Levels in A Preliminary Pre and Post Test Study on Adult Subjects - Diah Hastuti; Awal Prasetyo; Anzhari, Della Hashfi; Resti Ariani; Mutia Syafira; Anna Kartika Yuli Astuti; Rina Puspita (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Ideally, metabolic homeostasis is maintained through stable glucose regulation, balanced lipid metabolism, and effective uric acid clearance under conditions of minimal systemic inflammation. In real clinical conditions, aging and persistent low-grade inflammation frequently disrupt this balance, leading to hyperglycemia, dyslipidemia, and elevated uric acid levels. Current pharmacological management mainly emphasizes metabolic control and may not sufficiently address underlying tissue dysfunction or inflammatory processes. Platelet-rich plasma (PRP) is a blood-derived bioregenerative product containing growth factors with anti-inflammatory and regenerative properties, offering a potential supportive approach for metabolic regulation. Nevertheless, PRP administration has predominantly relied on invasive delivery methods. Nebulization provides a non-invasive pulmonary route that enables rapid systemic absorption, representing an alternative delivery strategy. Despite its potential advantages, clinical evidence regarding the metabolic effects of PRP delivered via nebulization remains limited, creating an urgent need for preliminary clinical evaluation. Therefore, this pre–post test study aimed to assess the effects of allogeneic PRP nebulization on random blood glucose, uric acid, and total cholesterol levels. Fourteen adult subjects received PRP nebulization for five consecutive days. The intervention resulted in a significant reduction in random blood glucose levels and mild decreasing trends in uric acid and total cholesterol without serious adverse events.